A Novel Co3O4/MnO2/C Electrode with Hierarchical Heterostructure for High‐performance Lithium‐Ion Batteries. Issue 44 (23rd November 2020) - Xu, Ying; Ye, Xiongbiao; Qiu, Yiwei; Gan, Chuanhai; Huang, Liuqing; Tang, Xueyuan; Luo, Xuetao
Abstract: Transition metal oxides (TMOs) are promising materials for next‐generation lithium‐ion batteries while the lithium storage and cycling stability of TMOs are still limited. Herein, a novel Co3 O4 /MnO2 /C composite using metal‐organic frameworks (MOFs) as sacrificial templates is reported. MnO2 and C shells are layer by layer coated on the MOF‐derived Co3 O4 /C samples via hydrothermal technique and heat treatment. When employed as anode materials for LIBs, the hierarchically heterostructured Co3 O4 /MnO2 /C composites incorporate the merits of Co3 O4, MnO2, and C, showing high Li storage performances at a current density of 0.2 A g −1 with an initial capacity of ∼1245.7 mAh g −1 and a reversible capacity of ∼854.9 mAh g −1 after 100 cycles, remarkable cycling stability, and excellent rate capability (almost 98 % recovery as the current density returns to the initial 0.2 A g −1, and especially, the specific capacity remains ∼587.6 mAh g −1 at a high current density of 2.0 A g −1 ). Abstract : A novel Co3 O4 /MnO2 /C composite with hierarchical heterostructure is prepared, where MnO2 and C shells coated layer‐by‐layer on the MOF‐derived Co3 O4 /C samples via hydrothermal technique and heat treatment. This synthesis method is facile and effective, without introducing additional redox solvents and templates. When employed as anode materials for LIBs, the Co3 O4 /MnO2 /C composite shows high electrochemical performances.